A sub-band division algorithm for ultra-wide bandwidth pulsar signals based on RFSoC - Du, Xu; Zhang, Hai-Long; Guo, Shao-Cong; Zhang, Ya-Zhou; Li, Jian; Wang, Jie; Ye, Xin-Chen; Wu, Han; Zhang, Ting (Frontiers in Astronomy and Space Sciences, 2024)
In order to realize the real-time processing and analysis of astronomical ultra-wide bandwidth signals, this study proposes a sub-band division algorithm based on RFSoC. The algorithm uses Kaiser window to design FIR prototype low-pass filter, adopts critical sampling polyphase filter bank to decompose ultra-wide bandwidth signal into several sub-bands, and encapsulates each sub-band into VDIF data frame and sends it to GPU server. The algorithm is implemented on RFSoC platform, and its effectiveness is verified by simulation and actual observation. The experimental results show that the algorithm can divide the astronomical ultra-wide bandwidth signal into multiple sub-bands in real time, packetize and transmit them to GPU. This research provides reproducible design and project for ultra-wide bandwidth signal sub-band division with low spectrum leakage and aliasing, high data accuracy, and fast processing speed.